2010
DOI: 10.1007/s11430-010-4052-6
|View full text |Cite
|
Sign up to set email alerts
|

China’s lakes at present: Number, area and spatial distribution

Abstract: Based on 11004 satellite images from CBERS CCD and Landsat TM/ETM, changes in the spatial characteristics of all lakes in China were determined following pre-established interpretation rules. This dataset was supported by 6843 digital raster images (1:100000 and 1:50000), a countrywide digital vector dataset (1:250000), and historical literature. Comparative data were corrected for seasonal variations using precipitation data. There are presently 2693 natural lakes in China with an area greater than 1.0 km 2 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
201
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 375 publications
(216 citation statements)
references
References 3 publications
1
201
0
2
Order By: Relevance
“…Our results also showed that higher fish species richness is predicted in lakes with sufficient precipitation and a larger surface area. This is in accordance with the actual situation in China where lakes distributed along the middle reach of the Yangtze River, such as Dongting lake, Liangzi lake, Hongze lake, Poyang lake, have a higher fish species richness because they owned appropriate temperature, abundant rainfall and relatively larger surface area (Cui and Li 2005;Ma et al 2011). While lakes distributed in the area with relative lower precipitation and temperature were predicted to have lower fish species richness.…”
Section: Prediction and Determinants Of Fish Species Richness In Chinsupporting
confidence: 85%
See 3 more Smart Citations
“…Our results also showed that higher fish species richness is predicted in lakes with sufficient precipitation and a larger surface area. This is in accordance with the actual situation in China where lakes distributed along the middle reach of the Yangtze River, such as Dongting lake, Liangzi lake, Hongze lake, Poyang lake, have a higher fish species richness because they owned appropriate temperature, abundant rainfall and relatively larger surface area (Cui and Li 2005;Ma et al 2011). While lakes distributed in the area with relative lower precipitation and temperature were predicted to have lower fish species richness.…”
Section: Prediction and Determinants Of Fish Species Richness In Chinsupporting
confidence: 85%
“…Lakes in China are covered with complex natural environments and large geological variations (Wang and Dou, 1998;Ma et al, 2011). In this study, a total of 135 lakes distributed across the mainland China were compiled as the main study area (with the coordinates across 21.9-48.9 • N and 81.2-132.6 • E, Fig.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Lakes are an important component of natural ecosystems in China, and play crucial roles in regulating floods, supplying drinking water, preserving biodiversity, and providing a freshwater fishery for food (Wang and Dou 1998). The latest lake survey found that 2693 natural lakes in China with an area of over 1.0 km 2 occupy *0.9 % of the country's territory (Ma et al 2011). For larger lakes over 10 km 2 in area, freshwater lakes make up 35 % of the total lake area, and have an average depth of approximately 2 m. Before the 1980s, most freshwater lakes had relatively good water quality and were eligible for drinking (Le et al 2010).…”
Section: Introductionmentioning
confidence: 99%